Differential effectiveness of two anxiety induction procedures in youth and older adult populations. - Nuevo, Roberto; Montorio, Ignacio; Cabrera, Isabel; Márquez, María; Izal, María (Anales de Psicología / Annals of Psychology, 2014)
In this study, we tested in older and younger adults the efficacy of two well-known procedures to experimentally induce anxiety: a) Velten self-statements combined with music; b) film scenes. We extended the previous findings in this field to the understudied area of mood induction in older adults. Fifty-seven older adults and 94 college students were randomly assigned to one of the experimental conditions or to a control group. Results indicated that both procedures were effective, according to a series of ANOVAs for several self-report, physiological, and behavioral measures. Likewise, the highest effect sizes were observed for the Velten procedure (g = .81 vs. g = .71), and the effects were significantly higher in younger (g = 1.0 in the Velten condition) than in older adults (g = .62), Q=4.25, 2(1), p = .0392. Both procedures were effective to induce inducting anxiety in both age groups, especially the Velten procedure in younger adults. Therefore, Velten self-statements combined with music may be very useful anxiety induction procedure for further research in controlled situations of emotions across the life-span.